Shifts in vegetation phenology along flyways entail varying risks of mistiming in a migratory songbird - Tamara Emmenegger (Ecosphere, 2016)
Abstract Long‐term shifts in vegetation phenology generally follow the pattern of global warming. Yet, topographical complexity and biome diversity cause uneven spatial trends in the phenological response of vegetation to climate change. If phenology changes similarly along migration routes, individuals may adequately respond by shifting the whole migration schedule to still time life history with local phenological events. On the contrary, phenological shifts that differ in direction or magnitude between sites can enhance the risk of mistiming, resulting in reduced survival and reproductive success and eventually population declines. We identified the direction and magnitude of long‐term shifts in vegetation phenology along avian migration routes, using remotely sensed vegetation data over 29 yr (1982–2010) to estimate the risk of mistiming for different sets of assumptions concerning cues and adaptability of migration timing. For this study, we used individual series of non‐breeding, spring stopover and breeding sites (determined by light‐level geolocation) of three European populations of Luscinia megarhynchos (Common Nightingale), an insectivorous Palearctic long‐distance migrant. The breeding populations in France, Italy, and Bulgaria are representatives for populations migrating on the western, central, and eastern flyway toward sub‐Saharan Africa. The direction and magnitude of phenological shifts differed between migration stages and across flyways and under most sets of assumptions, the resulting risk of mistiming was higher in the Western compared to Central and Eastern flyway. We emphasize that estimates for the risk of mistiming as resulting from phenological shifts highly depend on the cues that migrants use to time migratory progression and on the adaptive potential of the particular migratory species to react to phenological shifts.